Potential Output Growth in Emerging Market Countries : The Case of Chile - Roldos, Jorge (IMF Working Papers; Working Paper ;, 1997)
This paper estimates potential output and the sources of growth in Chile during 1970-96. Actual output is cointegrated with the quality-adjusted measures of capital and labor, and constant returns to scale cannot be rejected. The estimates of potential output show a positive output gap in the years when the Chilean economy was deemed to be overheated. In 1986-90, the quality-adjusted labor variable explains close to 60 percent of the growth rate of GDP, while during 1991-95 capital formation plays a dominant role. The contribution of TFP growth in Chile is relatively small, but, based on a comparison with European and East Asian experiences, it is expected to increase in the medium term.